2014
DOI: 10.3109/00016489.2014.919406
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic sudden sensorineural hearing loss in Japan

Abstract: ConclusionAn epidemiological survey of hospitals and private clinics in Japan regarding idiopathic sudden sensorineural hearing loss (SSNHL) revealed that the incidence of SSNHL was 60.9 per 100 000 population. There were more females than males in the younger generation.ObjectiveThe incidence of SSNHL varies largely by country. Because the Japanese criteria for diagnosing SSNHL have changed in accordance with those widely used in other parts of the world, a clinicoepidemiological study was undertaken using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 19 publications
(20 reference statements)
1
64
1
1
Order By: Relevance
“…Idiopathic SSNHL is reported to occur in 5-20 per 100,000 persons per year [1]. However, in Japan, the prevalence of idiopathic SSNHL was reported to be 60.9 per 100,000 persons, which is higher than the incidence reported in the previous study [1,2]. This difference may be caused by the method of data collection.…”
Section: Introductioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Idiopathic SSNHL is reported to occur in 5-20 per 100,000 persons per year [1]. However, in Japan, the prevalence of idiopathic SSNHL was reported to be 60.9 per 100,000 persons, which is higher than the incidence reported in the previous study [1,2]. This difference may be caused by the method of data collection.…”
Section: Introductioncontrasting
confidence: 55%
“…This difference may be caused by the method of data collection. In the previous study, private otolaryngology clinics were included in survey, and authors found that 65% of SSNHL patients only visited private clinics [2]. Epidemiological study of idiopathic SSNHL is therefore warranted in order to clarify risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of definite ALHL is reported to be 42.8-65.8 per 100,000 population in Japan [3] and to account for 18% of idiopathic SSNHL patients in Japan [4]. ALHL is a common presentation, but it has not received much attention in the literature with no large-scale epidemiological studies of ALHL, in particular, reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…The latest epidemiological survey of hospitals and clinics in Japan revealed that the incidence of idiopathic SSNHL was 60.9 per 100,000 population [1]. Little is known about the pathogenesis of idiopathic SSNHL, but several treatments have been proposed that cover the possible underlying mechanisms of disease, such as viral infection, intracochlear membrane rupture, and vascular compromise [2,3].…”
Section: Introductionmentioning
confidence: 99%